The little girl in a box - Bagas, Felinda V.; Aguirre, Aldy C. (Quezon City Adarna House, 2018)
"There was once a box, an ordinary cardboard box. But inside the box was something special. There was a little girl inside the box."
"This book is recommended for children ages 7 and above."
Keywords: Children's stories, Philippine (English).